The materiality of texts from ancient Egypt: new approaches to the study of textual material from the Early Pharaonic to the Late Antique period - Hoogendijk, F. A. J.; Gompel, Steffi M. T. van (Papyrologica Lugduno-Batava, 2018)
Intro -- Contents -- Preface -- Notes on Contributors -- Figures -- Abbreviated Literature -- Editorial Notation -- Chapter 1 The Material Authority of Written Texts in Pharaonic Egypt -- Chapter 2 The Platypus Paradox: An Archaeological Approach to Ancient Egyptian Writing Practices -- Chapter 3 Telling Them by Their Hands: What Palaeography Has to Offer Prosopography -- Chapter 4 The Body of the King and of the Goddess: Materiality in and through Manuals for Pharaoh from Tebtunis -- Chapter 5 Material Matters: Documentary Papyri and Ostraca in Late Ramesside Thebes -- Chapter 6 Writing on Ostraca: Considerations of Material Aspects -- Chapter 7 Ceramic Supports and Their Relation to Texts in Two Groups of Ostraca from the Fayum -- Chapter 8 Evolving Epigraphic Standards in the Field: Documenting Late Period and Graeco-Roman Egyptian Graffiti through Photogrammetry at Elkab -- Chapter 9 Revealing the Material World of Ancient Writing: Digital Techniques and Theoretical Considerations -- Bibliography -- Indexes -- Index of Egyptian Words -- Index of Greek Words -- Index of Sources -- Index of Subjects